Pembuatan Akun Pada Sosial Media Sosial Marketing Untuk Menunjang Pemasaran UKM Lorong - Hery Fadly (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
The research aims to see how important it is to create online social media accounts for alley SMEs and also how big the influence of social media marketing is on the marketing of alley UKM businesses. From the results, the researchers found that alley SMEs really needed marketing social media accounts so they could help do online marketing. Because it is felt that online marketing is an effective alternative way that will have a positive impact on increasing sales.